1984
DOI: 10.1203/00006450-198404001-01026
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Aids With Intravenous Gammaglobulin

Abstract: IMMUNOLOGYT h y m o s i n~l l e v e l s a r e markedly elevated in homosexual p a t i e n t s with AIDS o r AIDS-related complex (prodrome) a t a time when t h e i r T-cell function and OKT4/T8 r a t i o s a r e depressed. On the o t h e r

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Oleske et al treated a small number of children with IVIG and found that the incidence of serious bacterial infections was reduced, though the ultimate mortality was not altered (191). Rubenstein et al reported that patients treated with IVIG had an increase in the CD4/CD8 ratio and in lymphocyte transformation to phytohemagglutinin and pokeweed mitogen (192). Calvelli & Rubinstein (193) treated 14 children with an escalating dose of 50 to 300 mg/kg administered every 2 to 3 days and compared them with 27 patients not given IVIG.…”
Section: Secondary Defects Of Immunitymentioning
confidence: 99%
“…Oleske et al treated a small number of children with IVIG and found that the incidence of serious bacterial infections was reduced, though the ultimate mortality was not altered (191). Rubenstein et al reported that patients treated with IVIG had an increase in the CD4/CD8 ratio and in lymphocyte transformation to phytohemagglutinin and pokeweed mitogen (192). Calvelli & Rubinstein (193) treated 14 children with an escalating dose of 50 to 300 mg/kg administered every 2 to 3 days and compared them with 27 patients not given IVIG.…”
Section: Secondary Defects Of Immunitymentioning
confidence: 99%
“…Unfortunately, many individuals may have the misconception that infectious diseases occur only in adults. These diseases are not limited to adult populations (42). Our results showed some variability in the policies of agencies than treated only children or adolescents versus those agencies that served only adults or all ages.…”
Section: Resultsmentioning
confidence: 70%